The development and policies of ICT supporting educational technology in Singapore, Thailand, Indonesia, and Myanmar - Muhammad Takwin Machmud; Agung Purwa Widiyan; Noer Risky Ramadhani (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study has an objective to identify the development and policies of educational technology application in ASEAN countries. Through the literature review and analysis, this recent study has compared the issue of educational technology development and policies in ASEAN countries. The reviewing country has been chosen based on the Information and Communication Technology (ICT) index amongst the ASEAN countries, that are Singapore (as the highest rank), Thailand & Indonesia (as the middle rank), and Myanmar (as the lowest rank). The result of the study shows that the majority of the countries focused to improve network capabilities in supporting online learning, and the policies of each country showed a similarity in improving the technology equity for the learner. However, Singapore shows more advance technological implementation such as the application of broader Artificial Intelligence in classroom activity, while the use of Artificial Intelligence (AI) in Thailand and Indonesia still in developing progress. In conclusion, the technology education development in ASEAN countries has moved forward through the past year and the policies of educational technology for each country have been similar in strengthening the ASEAN plan.